DESKRIPSI POLA MAKAN PENDERITA MAAG PADA MAHASISWA JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - fitri, ririn; Yusuf, liswarti; yuliana, yuliana (Journal of Home Economics and Tourism, 2013)
This research aimed to describe diet pattern for student with stomach disorder in KKFT-UNP, concerning in type of food that student mostly consumed and meal timefrequency. The population is 39 students of KK FT-UNP that being diagnosed bystomach disorder, sample is taken by total sampling technique.The result shows thatdiet pattern based on food’s types that had been recommended are 22 types, but only17 types is consumed by 35.9% respondent (medium category). In non-recommendedfood amount to 50 types, and 44 types are consumed by 35.9% respondent (highcategory). Whereas, 87.2% (very low category) respondent rarely and didn’tconsumed recommended food. The frequency of respondent consume nonrecommendedfoodis53.8%(highcategory)with theintensitiesareoftenandalways.Basedon regularity of meal from respondent shows that 38.5% is not eatingregularly; 33.3% is lack of breakfast; 59.0% eat two times a day and 51.3% didn’t eatat mealtime; 46.1% always eat late, and 51.3% eat after they starving (very lowcategory). Keywords: stomach disorder, diet pattern, university student.